Dietary classification of extant kangaroos and their relatives (Marsupialia: Macropodoidea). (14th July 2015) - Arman, Samuel D.; Prideaux, Gavin J.
Abstract: Kangaroos and kin (superfamily Macropodoidea) are the principal endemic herbivores of Australia and the most diverse radiation of marsupial herbivores ever to have evolved. As is typical of other herbivore groups (e.g. bovids), dietary niches span fruit, fungi, dicot leaves and monocot grasses in both specialists and generalists, but to date dietary classification has been largely ad hoc and poorly tied to actual dietary ecological data. Here we provide a simple dietary classification of the Macropodoidea based on an extensive literature survey. Intake of four major dietary items – grasses, dicot leaves, fruits and seeds, and fungi – was assessed using proportional intake for 19 species and categorical (ranked intake) data for 37 species. Statistical comparisons with cluster and principal components analyses aligned species into four dietary groups. Members of the first group have diets that primarily consist of fungi and fruits. Relative proportions of grasses to dicot leaves separate the remaining species into browser (more than 70% dicots), grazer (more than 70% grasses) and mixed feeder groups. Comparison of our diet‐based classification with a prevailing scheme based on dental morphology suggests that most species with what has traditionally been viewed as a 'browser‐grade dentition' are actually mixed feeders. This suggests that either morphology and diet are not tightly linked or that morphological differences between the dentitions of browsers and mixed feeders are subtle and have been overlooked. A positive correlation was found between body mass and average proportional intake of grass in the diet of macropodoids. This parallels the situation found in bovids, as well as the percentage cut‐off between dietary groups. These trends suggest that some underlying ecophysiological constraints may influence food choice in mammalian herbivores providing useful pointers to the diets of extinct taxa.